Low-concentration atropine (0.01%) on quantitative contrast sensitivity function in Chinese children with myopia - Yu-Hao Ye; Yi-Yong Xian; Fang Liu; Zhong-Lin Lyu; Xing-Tao Zhou; Jing Zhao (International Journal of Ophthalmology)
AIM: To investigate the effect of 0.01% low-concentration atropine (LA) on quantitative contrast sensitivity function (qCSF) in children with myopia. METHODS: This paired case-control study included 90 eyes of 58 children who were sex-, age-, and refraction-matched and equally divided into two groups: the 0.01% LA group had undergone 6mo use of daily 0.01% atropine and control group was naïve to LA. Routine ophthalmic examinations and qCSF test without refractive correction were performed. Two groups were compared in monocular and binocular qCSF parameters, including the area under logCSF, CSF acuity, and contrast sensitivity (CS) at 1.0-18.0 cycle per degree (cpd). RESULTS: In the monocular comparison, the CSF acuity of the LA group was significantly higher than that of the control group (7.58±5.51 vs 6.37±4.22 cpd, P<0.05). The subgroup analysis showed that in the 6-9y group, CSF acuity was significantly higher in the LA group than the control group (8.76±6.19 vs 6.54±4.25 cpd, P<0.05), and in the Female group, low refraction sphere group, and high refraction cylinder group, the CS at high spatial frequencies (12.0 and 18.0 cpd) were significantly higher in the LA group than in the control group (all P<0.05). In the binocular test, CSF acuity and CS at 12.0 cpd were significantly higher in the LA group than in the control group (10.95±7.00 vs 8.65±5.12 cpd; 0.17±0.33 vs 0.06±0.16, respectively; both P<0.05). CONCLUSION: Use of LA may result in improved CS in children with early onset myopia.